2019
DOI: 10.1093/schbul/sbz111
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic Dysfunctions in Brain Modules Across Patients with Schizophrenia, Bipolar Disorder, and Major Depressive Disorder: A Connectome-Based Study

Abstract: Psychiatric disorders, including schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD), share clinical and neurobiological features. Because previous investigations of functional dysconnectivity have mainly focused on single disorders, the transdiagnostic alterations in the functional connectome architecture of the brain remain poorly understood. We collected resting-state functional magnetic resonance imaging data from 512 participants, including 121 with SCZ, 100 with BD, 108 with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 89 publications
5
55
1
Order By: Relevance
“…We observed that several specific regions in the SMN/VIS and DMN shifted from the periphery to the center in the hierarchical space, implying a trend towards dedifferentiated connection profiles between these systems. This phenomenon is comparable to previous findings from connectome modular studies in MDD, where hyperconnections were found among the primary systems and the transmodal DMN and FPN (20, 23, 51). In a hierarchical organization, the primary brain systems receive external stimulation signals and process them into abstract representations (52), while the transmodal brain systems integrate the processed information with internal control, memory, and emotion to guide interactions with the external environment (12, 52).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that several specific regions in the SMN/VIS and DMN shifted from the periphery to the center in the hierarchical space, implying a trend towards dedifferentiated connection profiles between these systems. This phenomenon is comparable to previous findings from connectome modular studies in MDD, where hyperconnections were found among the primary systems and the transmodal DMN and FPN (20, 23, 51). In a hierarchical organization, the primary brain systems receive external stimulation signals and process them into abstract representations (52), while the transmodal brain systems integrate the processed information with internal control, memory, and emotion to guide interactions with the external environment (12, 52).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the principal primary-to-transmodal gradient changes across brain development (17) and is altered in brain disorders such as autism (18). In patients with MDD, R-fMRI studies have revealed alterations in functional activity and connectivity involving the primary visual and sensorimotor systems (6,(19)(20)(21) and transmodal systems such as the default mode network (DMN) and frontoparietal network (FPN) (19,20,(22)(23)(24). However, no studies have reported whether and how the principal primary-to-transmodal gradient of the functional connectome is disrupted in this clinical population.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced functional connectivity between the amygdala and dorsolateral prefrontal lobe of adolescents with schizophrenia and depression is a common change in conditions paralimbic GM volume atrophy is a common brain alteration found in patients with depression, bipolar disorder, and schizophrenia (Chang et al., 2018). Recent studies have shown that schizophrenia, depression, and bipolar disorder have the following common characteristic alterations: (a) decreased modularization of the whole brain; (b) decreased activity of frontal–parietal network, subcortical network, and visual network, along with decreased modularization of the sensorimotor network; and (c) the increased connection coefficients between certain networks, especially networks of the dorsolateral prefrontal lobe, angular gyrus, and thalamus (Ma et al., 2019). Sambataro et al .…”
Section: Depressive Symptoms In Schizophreniamentioning
confidence: 99%
“…For example, major depressive disorder is commonly associated with anxiety symptoms, but these also occur in bipolar disorder and schizophrenia. Recent studies have used brain imaging and transdiagnostic approaches to characterise the neural basis of the shared symptoms 171819. Resting state fMRI data showed that patients with major depressive disorder, bipolar disorder, and schizophrenia had common brain functional deficits 18.…”
Section: Diagnostic Confusionmentioning
confidence: 99%
“…Recent studies have used brain imaging and transdiagnostic approaches to characterise the neural basis of the shared symptoms. 17 18 19 Resting state fMRI data showed that patients with major depressive disorder, bipolar disorder, and schizophrenia had common brain functional deficits. 18 More generally, recent studies proposed a general psychopathology factor ( p factor) to describe a shared vulnerability to a broad range of symptoms across mental disorders, 20 and a higher p factor was associated with diminished activation of the frontal pole, anterior cingulate cortex, and anterior insula during executive tasks.…”
Section: Diagnostic Confusionmentioning
confidence: 99%